2013
DOI: 10.1097/dcr.0b013e3182a69a3b
|View full text |Cite
|
Sign up to set email alerts
|

Modified Wong's Classification Improves the Accuracy of Rectal Cancer Staging by Endorectal Ultrasound and MRI

Abstract: With use of the modified Wong's classification proposed in this study, the overall accuracy of preoperative imaging in assessing T staging of rectal cancer is substantially improved, especially when endorectal ultrasound and MRI stage match, enhancing the selection of patients for neoadjuvant radiochemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…In another study, good agreement was found between ultrasound and MRI in classifying extramural spread into early and advanced using a cut‐off of 5 mm . More recently a maximum tumour thickness with a cut‐off of 19 mm, detected by ultrasound, has been suggested as a more realistic prognostic parameter than the measurement of the radial extension into the mesorectal fat . Owing to the limitation of ultrasound in imaging tissue lying 10 mm or more beyond the rectal wall, it is mostly used in the assessment of early tumours for local treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, good agreement was found between ultrasound and MRI in classifying extramural spread into early and advanced using a cut‐off of 5 mm . More recently a maximum tumour thickness with a cut‐off of 19 mm, detected by ultrasound, has been suggested as a more realistic prognostic parameter than the measurement of the radial extension into the mesorectal fat . Owing to the limitation of ultrasound in imaging tissue lying 10 mm or more beyond the rectal wall, it is mostly used in the assessment of early tumours for local treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Kocaman et al [32] found overstaging in overall 8/50 cases, with 4/15 patients staged from T2 to T3/4 (26.7%). In a prospective study comparing standard local TN classification and a modified Wong's classification, MRI overstaging was revealed to be therapy-relevant in 16/42 cases (38%) [33]. The N category was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] this explains the oncologic inferiority of le, with local recurrence as the most common pattern of failure, ranging from 20% to 30% as reported by several authors. the accuracy of endorectal ultrasound (eRus) and/or mRi is 60% to 80% at its best, with an inability to find lymph nodes <5 mm in size, which have the potential to harbor metastasis.…”
Section: Outcomes Of Salvage Surgery For Cure In Patients With Locallmentioning
confidence: 99%